2014
DOI: 10.1093/eurheartj/eht571
|View full text |Cite
|
Sign up to set email alerts
|

Mendelian randomization of blood lipids for coronary heart disease

Abstract: AimsTo investigate the causal role of high-density lipoprotein cholesterol (HDL-C) and triglycerides in coronary heart disease (CHD) using multiple instrumental variables for Mendelian randomization.Methods and resultsWe developed weighted allele scores based on single nucleotide polymorphisms (SNPs) with established associations with HDL-C, triglycerides, and low-density lipoprotein cholesterol (LDL-C). For each trait, we constructed two scores. The first was unrestricted, including all independent SNPs assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

35
429
3
11

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 638 publications
(490 citation statements)
references
References 34 publications
35
429
3
11
Order By: Relevance
“…However, an HDL‐C influence on CHD is itself paradoxical. While observational studies consistently report a protective association of high blood HDL‐C levels with lower CHD risk, previous MR studies show that HDL‐C is not a causal risk factor for CHD 48, 57. Furthermore, a recent study has reported that a loss‐of‐function variant in scavenger receptor BI ( SRB1 ) raises HDL‐C and increases CHD risk 58.…”
Section: Discussionmentioning
confidence: 99%
“…However, an HDL‐C influence on CHD is itself paradoxical. While observational studies consistently report a protective association of high blood HDL‐C levels with lower CHD risk, previous MR studies show that HDL‐C is not a causal risk factor for CHD 48, 57. Furthermore, a recent study has reported that a loss‐of‐function variant in scavenger receptor BI ( SRB1 ) raises HDL‐C and increases CHD risk 58.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic studies have shown that elevated triglycerides correlate with elevated cardiovascular risk,4, 5 and the American Heart Association has long recognized that elevated triglycerides are an important marker of cardiovascular risk 6. More recently, genetic,7, 8, 9, 10, 11, 12, 13 genome‐wide analysis,14, 15, 16, 17 and mendelian randomization18, 19, 20, 21, 22 studies have suggested a causal role for triglycerides as a modifiable risk factor in the development and progression of ASCVD. Analyses from clinical data have demonstrated that lower on‐treatment triglycerides correlate with reduced cardiovascular risk 23, 24…”
mentioning
confidence: 99%
“…These variants have been incorporated into so-called allele scores for use as instruments for their levels in Mendelian randomization experiments (10). Allele scores appear to provide more powerful genetic instruments for complex traits than single variants as the combination of variants has a greater effect on lipid levels and has been used effectively to investigate causal links between lipid moieties and cardiovascular disease (11,12). In their analysis, Fall et al minimized potential confounding between lipid fractions by constructing allele scores with maximal specificity for their index trait.…”
mentioning
confidence: 99%